Peningkatan Laba Penjualan Melalui Sosialisasi Manajemen Keuangan Pada Umkm Di Kabupaten Kepahiang - Sintia Safrianti; Sintia Safrianti; Veny Puspita; Janusi Waliamin; Dwi Oktavallyan Saputri (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
This community service activity was carried out at RAPINDO COFFEE which is located on Jalan Pensiunan, Kepahiang District, Kepahiang Regency with a total of 15 participants from Micro and Medium Enterprises.. Micro, Small and Medium Enterprises in Kepahiang Regency had not implemented good and complete bookkeeping in running their business. It could be said that they still used simple financial bookkeeping. In addition, micro, Small and medium enterprises in Kepahiang Regency only use a manual agenda book which is divided into two books, namely a financial notebook at home and a business activity notebook. Furthermore, there is no use of financial management related to 4 indicators, namely budget use, financial recording, financial reporting and financial control. Therefore, the purpose of this community service is to increase the knowledge of Micro, Small and Medium Enterprises actors regarding financial management. This community service activity is carried out using 4 methods, namely problem identification, lectures, discussions, monitoring and evaluation. The results of this community service have shown that the financial management knowledge of Micro, small and Medium enterprises in Kapahian District has increased. This is very useful in carrying out their business.